Toward Safe and Efficient Recovery of Gas Munitions Dumped at Sea - Rowiński Lech; Truong Thanh Hai; Nguyen Phuoc Quy Phong (Polish Maritime Research, 2023)
The proposal of a system for the safe recovery of unexploded ordnance (UXO), chemical weapons (CW) and chemical warfare agents (CWA) dumped at sea mainly after WWI and WWII is described in this work. The proposed solution addresses the tasks required to neutralise thousands of tons of dumped material and the currently available solutions and proposed ideas. Requirements concerning the features of a recovery system are defined and scrutinised, these being intended to ensure the safety of this phase of the UXO/CW neutralisation process. To meet this requirement, the concept of a remotely operated, two-component working size underwater vehicle is proposed, supplemented by a properly sized and outfitted surface platform that is an important part of the recovery system. Finally, the basic components of the proposed system configuration are characterised, together with their functions during the recovery of dangerous CWA-related objects.